2021
DOI: 10.1007/s42379-021-00095-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on health of the older persons in Bangladesh

Abstract: The COVID-19 is impacting the health of the population, including older persons. Available evidence shows that older people are highly vulnerable and more likely to have adverse health outcomes. In Bangladesh, the older population is rapidly increasing, living with various disadvantaged socio-economic conditions, including inadequate access and healthcare services. These disparities are likely to increase during the COVID-19, resulting in high morbidity and mortality among them. Thus, we have examined the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A study conducted in Saudi Arabia also showed that older individuals had higher knowledge about COVID-19 (59). According to the World Health Organization (WHO) and some existing literatures, older society is at highest risk of contracting this virus, and more than 95% of the related death is attributed to this age group (60)(61)(62). This may be because older people are more likely to catch viruses or diseases such as COVID-19 due to poor immunity, so they could be more cautious about COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Saudi Arabia also showed that older individuals had higher knowledge about COVID-19 (59). According to the World Health Organization (WHO) and some existing literatures, older society is at highest risk of contracting this virus, and more than 95% of the related death is attributed to this age group (60)(61)(62). This may be because older people are more likely to catch viruses or diseases such as COVID-19 due to poor immunity, so they could be more cautious about COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health is a severely neglected issue in Bangladesh, specifically among older people. The pandemic disrupted the already existing inadequate mental health services [27], especially among older people [28], increasing their vulnerability to anxiety and depression. Evidence indicates that the COVID-19 pandemic and its impacts on Bangladeshi older people have not ended yet due to several factors, including but not limited to, inadequate and untimely measures for controlling coronavirus infection [7], low vaccination coverage among older people [29], irregularities, and limited preparedness of the health sector [30].…”
Section: Open Accessmentioning
confidence: 99%
“…During the initial literature search, we found that there were very few studies discussing women's empowerment–related issues in FRH control in Bangladesh. 17 , 38 , 45 , 48 , 49 , 50 , 52 , 53 , 54 , 57 Most of these studies were cross-sectional in nature, and we did not find any review-based studies on this topic. As a first initiative to address all these issues, we reviewed several Bangladesh-based articles from different time periods to provide a more comprehensive understanding of the relationship between women's empowerment and fertility and reproductive behavior.…”
Section: Discussionmentioning
confidence: 94%
“… 65 , 66 , 67 Research suggests that higher levels of education are associated with a lower number of children and reduced progression to parity-specific fertility when compared with women with lower education levels. 48 A study conducted by Islam and Nesa 52 in 2009 revealed that across all education levels, rural areas had higher TFRs and total marital fertility rates than urban areas. Similarly, a study by Haq et al 54 in 2019 found that women who resided in rural areas had a higher tendency to have more children than their urban counterparts.…”
Section: Discussionmentioning
confidence: 99%